2018
DOI: 10.1016/j.bbagrm.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of ATM and ATR by SMARCAL1 and BRG1

Abstract: The G2/M checkpoint is activated on DNA damage by the ATM and ATR kinases that are regulated by post-translational modifications. In this paper, the transcriptional coregulation of ATM and ATR by SMARCAL1 and BRG1, both members of the ATPdependent chromatin remodeling protein family, is described. SMARCAL1 and BRG1 colocalize on the promoters of ATM and ATR; downregulation of SMARCAL1/BRG1 results in transcriptional repression of ATM/ATR and therefore, overriding of the G2/M checkpoint leading to mitotic abnor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 73 publications
2
17
0
Order By: Relevance
“…The upstream DDR checkpoint kinases ATM and CHK2 have been reported to be increased in certain human pre-malignancies in vivo [ 46 ]. ATM showed a consistent upregulation in total protein ( Figure 5 b) in all PPOLs and OSCCs and has been reported following DNA damage before [ 47 ]. However, only one MPPOL line, D25, showed an increase in phosphorylation at serine 1981 (ATM-P) relative to NOKs.…”
Section: Resultssupporting
confidence: 82%
“…The upstream DDR checkpoint kinases ATM and CHK2 have been reported to be increased in certain human pre-malignancies in vivo [ 46 ]. ATM showed a consistent upregulation in total protein ( Figure 5 b) in all PPOLs and OSCCs and has been reported following DNA damage before [ 47 ]. However, only one MPPOL line, D25, showed an increase in phosphorylation at serine 1981 (ATM-P) relative to NOKs.…”
Section: Resultssupporting
confidence: 82%
“…Accumulation or persistence of R-loops could be involved in this mechanism, suggesting the need to assess whether R-loops preferentially accumulate at affected genes. Of note, both ATR- and ATM-dependent signalling have been found to be dysfunctional in cells lacking SMARCAL1, especially following induction of DSBs by doxorubicin treatment (Patne et al, 2017; Sethy et al, 2018). We, and others, have found higher activation of ATM in the absence of SMARCAL1 under unperturbed cell growth or upon perturbed replication (Couch et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The disease is caused by bi-allelic mutations in the SMARCAL1 gene (Boerkoel et al, 2002). Although SMARCAL1 encodes for a protein homologous to the SNF2 family of chromatin remodelling factors and SMARCAL1 has been involved in transcriptional regulation (Patne et al, 2017; Sethy et al, 2018; Sharma et al, 2016), recent works proved that SMARCAL1 is critical during processing of DNA structures at replication forks to promote formation of replication intermediates through its ATP-driven strand-annealing activity (Bansbach et al, 2009; Ciccia et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Fun30, an ATP-dependent chromatin remodeling protein, mediates not only DNA end resection but also modulates transcriptional regulation [ 7 , 26 , 27 , 28 ]. Previously, we had shown that in mammalian cells the DNA damage response pathway is transcriptionally regulated by ATP-dependent chromatin remodeling proteins [ 29 , 30 , 31 ]. Therefore, we investigated whether Fun30 regulates genes involved in the DNA damage response pathway in C. albicans .…”
Section: Resultsmentioning
confidence: 99%